2012
DOI: 10.1007/s10661-012-3012-3
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residues in vegetable samples from the Andaman Islands, India

Abstract: Vegetable samples of brinjal, okra, green chilli, crucifers, and cucurbits collected from farmers' field were tested for the presence of organochlorine (OC), organophosphorus (OP), and synthetic pyrethroid (SP) compounds using a gas chromatograph equipped with electron capture and flame thermionic detectors. Of the samples tested, 34.0% were found to have pesticide residues. Among the OC compounds, α-endosulfan, β-endosulfan, and endosulfan sulfate were detected in 14.5% of the samples with residues. These wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 17 publications
5
39
2
1
Order By: Relevance
“…It has been banned in Western countries like the USA, but is still widely used in some African and Asian countries because of its good insecticidal efficacy and low price (Tariq et al 2004;Kumari et al 2007;Krause et al 2013). Monocrotophos residues in brinjal, okra, cucurbits, crucifers, and green chili were found to be 0.023-1.140 mg/kg (Swarnam and Velmurugan 2013) on the Andaman Islands, India, and its concentration in the industrial wastewater near Lucknow City, India, was reported to be 8.32 ± 3.9 lg/L (Anjum and Malik 2013). Monocrotophos residues can enter the aquatic environment through surface runoff or be absorbed by organisms via the food chain and thereby alter the genetic materials of exposed organisms and induce DNA damage (Saleha Banu et al 2001;Ali and Kumar 2008), which includes DNA single-strand breaks (SSB), double-strand breaks (DSB), alkali-labile sites (ALS), DNA base oxidation, DNA-protein cross-links, and DNA-DNA cross-links (Ribas-Maynou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been banned in Western countries like the USA, but is still widely used in some African and Asian countries because of its good insecticidal efficacy and low price (Tariq et al 2004;Kumari et al 2007;Krause et al 2013). Monocrotophos residues in brinjal, okra, cucurbits, crucifers, and green chili were found to be 0.023-1.140 mg/kg (Swarnam and Velmurugan 2013) on the Andaman Islands, India, and its concentration in the industrial wastewater near Lucknow City, India, was reported to be 8.32 ± 3.9 lg/L (Anjum and Malik 2013). Monocrotophos residues can enter the aquatic environment through surface runoff or be absorbed by organisms via the food chain and thereby alter the genetic materials of exposed organisms and induce DNA damage (Saleha Banu et al 2001;Ali and Kumar 2008), which includes DNA single-strand breaks (SSB), double-strand breaks (DSB), alkali-labile sites (ALS), DNA base oxidation, DNA-protein cross-links, and DNA-DNA cross-links (Ribas-Maynou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This results in OPP contamination in environmental media including soil, groundwater, and surface water (Roverdatti 2001;Kanekar et al 2004). Among pesticides under OPP, profenofos (O-4-bromo-2-chlorophenyl O-ethyl S-propyl phosphorothioate), C 11 H 15 BrClO 3 PS, is one of OPPs broadly used in many countries, such as Thailand, Vietnam, and India (Swarnam and Velmurugan 2013;Toan et al 2013). Profenofos (PF) is normally used for pest control in cotton, fruit, chili, and vegetable cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have concentrated on the regulatory effects of cytochrome P450, glutathione, and the ABC transporter protein on pesticide metabolism in plants (Shiota et al, 1996;Brazier-Hicks et al, 2008;Meng et al, 2016). The GC technique has been widely used to analyze pesticide residues of relatively small molecular weight, high volatility, and heat-stability (González-Rodríguez et al, 2008;Swarnam and Velmurugan, 2013). In our study, GC was used to analyze the levels of propamocarb residue in cucumber fruits.…”
Section: Discussionmentioning
confidence: 99%